2012
DOI: 10.21608/jppp.2012.83739
|View full text |Cite
|
Sign up to set email alerts
|

IMPACT OF INTERCROPPING OF CITRONELLA GRASS (Cymbopogon schoenanthus cyperles) AND LEMON GRASS (Cymbopogon citratus stapf) OF THE INFESTATION LEVEL OF INSECT PESTS AND ACARI IN COWPEA CROP AT KAFR EL-SHEIKH REGION .

Abstract: In 2010 and 2011 cowpea seasons, experiments were carried out to investigate the effect of intercropping between cowpea and each of Citronella grass and lemon grass on the populations of insect pests attacking cowpea. Intercropping in general, reduced the pests complex in cowpea fields. These reductions were 94.34-97.78, 75.98-80.19 and 50.64-58.37% in case of intercropping of Citronella grass with one, two and three rows of cowpea, respectively. The corresponding values in case of lemon grass were 97.92-99.11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…(eggs, nymphs and adults) compared to kidney bean solid. Kassem et al (2012) found that intercropping between cowpea and each of citronella grass and lemon grass reduced the populations of insect pests attacking cowpea. Intercropping in general, reduced the pest complex in cowpea fields.…”
Section: Discussionmentioning
confidence: 99%
“…(eggs, nymphs and adults) compared to kidney bean solid. Kassem et al (2012) found that intercropping between cowpea and each of citronella grass and lemon grass reduced the populations of insect pests attacking cowpea. Intercropping in general, reduced the pest complex in cowpea fields.…”
Section: Discussionmentioning
confidence: 99%